Pendampingan Optimalisasi Media Sosial untuk Meningkatkan Produktivitas di Kalangan UMKM Warga Kecamatan Lumbang Probolinggo - Ibad, M. Nashoihul; Dewantara, Muhammad Iqbal (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to assist Micro, Small, and Medium Enterprises (MSMEs) in Lumbang District, Probolinggo Regency, in optimizing the use of social media to increase business productivity. The focus of the training is to provide participants with understanding and skills regarding effective digital marketing strategies, especially through the Instagram platform. With the training module titled "Instagram for Business," participants gained practical guidance in managing social media accounts as well as creating engaging and relevant content to expand their market. The results of the training showed a significant improvement in participants' understanding of the use of social media as a marketing tool. The obstacle found during the implementation was the lack of communication between the committee and the local community, so that some participants could not attend. Overall, however, this activity has had a positive impact, helping MSMEs increase productivity and expand market reach through social media. This report is prepared as evaluation material and scientific publications for the development of future activities.